1976
DOI: 10.1161/01.cir.54.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial blood flow in congestive and hypertrophic cardiomyopathy: relationship to peak wall stress and mean velocity of circumferential fiber shortening.

Abstract: SUMMARY Myocardial blood flow/unit mass (MBF) and the determinants of myocardial oxygen consumption were measured in seven control subjects (group I) and 15 patients (pts) with cardiomyopathy (CM), group II (group Ila-congestive CM: 10 pts; group Ilb-hypertrophic CM: 5 pts). In group I left ventricular (LV) MBF was 64±8 (SD) ml/lOg -min; it was significantly lower in Ila (45 ± 15 ml/lOOg. min, P < 0.01) and IIb (39±7 ml/100g min, P < 0.01). However, calculated total LV flow (LV mass X MBF) was increased in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(36 citation statements)
references
References 61 publications
1
33
0
2
Order By: Relevance
“…The present study examined responses to acetylcholine after 2 wk ofexperimental CHF and found that the threshold for relaxation to acetylcholine was decreased significantly in coronary arteries but was unchanged in femoral and renal arteries. Increases in blood flow in canine systemic arteries result in augmented endothelium-dependent relaxations to acetylcholine (26) and studies, while controversial (2,27), have demonstrated increased myocardial blood flow in CHF. A similar mechanism may operate to produce the augmented response to acetylcholine reported in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study examined responses to acetylcholine after 2 wk ofexperimental CHF and found that the threshold for relaxation to acetylcholine was decreased significantly in coronary arteries but was unchanged in femoral and renal arteries. Increases in blood flow in canine systemic arteries result in augmented endothelium-dependent relaxations to acetylcholine (26) and studies, while controversial (2,27), have demonstrated increased myocardial blood flow in CHF. A similar mechanism may operate to produce the augmented response to acetylcholine reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed in two groups of mongrel dogs (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) kg) that were fed standard diet and allowed free access to water. Dogs that had not been operated on served as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Results showed a depressed MBF of 0.45F0.15 [30] and of 0.49F0.17 ml/ min/g [29], a normal flow of 0.78F0.17 ml/min/g [31] and a high normal flow of 1.02F0.21 ml/min/g [21]. This great variability was probably due to the different methods used and different states of the disease.…”
Section: Characterization Of Global Mvo 2 and Mbf In Dcm Patientsmentioning
confidence: 96%
“…Measurements of MBF in nonischemic DCM have been performed with microspheres [29], with 13 N-ammonia [21], or inert gas washout techniques [30,31]. Results showed a depressed MBF of 0.45F0.15 [30] and of 0.49F0.17 ml/ min/g [29], a normal flow of 0.78F0.17 ml/min/g [31] and a high normal flow of 1.02F0.21 ml/min/g [21].…”
Section: Characterization Of Global Mvo 2 and Mbf In Dcm Patientsmentioning
confidence: 99%
“…Impairment of coronary flow reserve has been shown in patients with dilated cardiomyopathy (DCM) despite normal epicardial coronary arteries (1)(2)(3)(4)(5). Various methods have been used to measure coronary flow in these patients, including coronary sinus thermodilution (3,6), intracoronary Doppler flow wire (7)(8)(9), position emission tomography (PET) (10,11), and transesophageal echocardiography (12).…”
Section: Introductionmentioning
confidence: 99%